(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
In this paper, we investigated factors affecting movement restriction while wearing stab-resistant vests with the aim of improving their comfort. We measured the contact area and pressure between the vest and a dummy, and performed sensory tests for movement restriction in the wearer's arms and upper body using four vests of different sizes, weight and types of stab-proof material. The pressure distribution of the vests on a dummy was measured and cross-sections of dummy-worn vests were obtained by 3D scan. For these measurements, we controlled the tightness value, the ratio between vest waist circumference and dummy. In order to check the influence of vests on the movement of the arm and upper body, subjects evaluated movement restriction and the feeling of pressure on the waist, chest, abdomen and back. We discovered that vests tend to hang on the neck point, shoulder, chest and back. The pressure on the chest increased with increasing tightness value, while the abdomen was under pressured to a forward bending position. Thus, shorter stab-resistant materials at the vest front have less movement restriction. In the arms, subjects reported less movement restriction when they felt that the shoulder area was softer. Therefore, we discovered that contact area and pressure should be considered in the design of stab-resistant vests to improve the comfort of the wearer.